Environmental controls on bioluminescent dinoflagellate density, in Laguna Grande, Fajardo, Puerto Rico - Govender, Yogani; Jury, Mark (Revista de Biología Tropical, 2024)
Introduction: Bio bays in Puerto Rico play an important socio-economic role and declines in dominant bioluminescent dinoflagellate Pyrodinium bahamense are concerning. Studies show erratic blooms with is weak correlation to in situ environmental factors. Our study examines shorter field and longer proxy records on dinoflagellate density at Laguna Grande de Fajardo (LGF). Objectives: To quantify temporal changes in dinoflagellate density in a long-term monitoring study, understand how the marine environment modulates those changes, and determine the wider impacts of a fluctuating climate and extreme events on proxies for dinoflagellate density. Methods: Bimonthly samples were collected from 2016 to 2021 at three sampling sites in LGF. Dinoflagellates density was estimated by Sedgewick Rafter counting cells. Environmental conditions were obtained from Rio Fajardo 5007100 station and NOAA buoy 41056. Marine climate and biotic proxies were obtained from remote sensing measurements. Kruskal Wallis, Spearman correlations and cross-correlations in the shorter field and longer proxy records were used to evaluate environmental controls on LGF dinoflagellate blooms. Results: Six years of field monitoring densities found a low period in 2016-2017, frequent and intense blooms in 2018-2021 punctuated by hurricanes. Generally low values were recorded in late winter in contrast with higher values in late summer (Aug-Nov). Light winds and mixed layer response to seasonal warming in the form of high tides and low salinity, were found to sustain dinoflagellate reproduction. Conclusions: Bioluminescent dinoflagellates are vital to coastal tourism and require resource management. LGF results show that: 1) dinoflagellate counts fluctuate widely, 2) fluorescing dinoflagellates are sensitive to environmental conditions because of limited seasonality and narrow physiological range, 3) hurricanes play a role by ‘raking and refreshing’ the coastal lagoon for subsequent biotic reproduction, and 4) intra-seasonal fluctuations of density and proxies relate to air-sea thermodynamic conditions, the salinity budget and sea level.